ITALIAN MANAGEMENT METHOD - Abdusattorov, Davron (Science technology&Digital finance, 2023)
In this article, an attempt was made to reflect complete information about the Italian method of management and its enterprise management, and we tried to give a smaller overview of the reforms being carried out in the state.